Impact of income-detection technology and other factors on aggregate income tax evasion:the case of the United States - Cebula, Richard J. (PSL Quarterly Review, 2012)
This study empirically investigates the impact of improving income-detectiontechnology, as well as a variety of other factors, on aggregate income taxevasion. The study focuses on the U.S., using available data for the 1975-97 period. The empirical findings indicate that improving income-detection technology appears to have significantly reduced the degree of aggregate income-tax evasion in theU.S. over time. In addition, the estimates indicate that federal income tax evasionappears to be an increasing function not only of the federal personal income tax rate but also of the public's dissatisfaction with government. Furthermore, income taxevasion appears to be a decreasing function both of penalties imposed by the IRS on unpaid taxes and IRS audit rates. JEL Codes: H24, H26, H31